Prospects of Cross-Border Cooperation in Europe: Capacity-Building and the Operating Principle of “Horizontal Subsidiarity” - Joachim Beck (Central European Public Administration Review)
Based on a reflection of the seven central challenges which all cross- border territories in Europe are facing in practice, the article analyses how cross-border cooperation in Europe could be improved in the future. Two central fields are interpreted in this regard: training/facilitating and applied interdisciplinary research. The article suggests that a more effective cross-border policymaking of the future depends on a systemic capacity-building, based on the new operating principle of »horizontal subsidiarity«. For the moment being, cross-border cooperation is only a functional sub-system, created by and largely depending on contributions coming from the states involved. Horizontal subsidiarity, combined with new approaches such as territorial impact assessment, multi-level governance or joint interest representation would allow for a better development of an integrated cross-border policymaking, based on the real challenges and potentialities of a 360° perspective on the cross-border territory.